Peningkatan Prestasi Akademik Siswa melalui Strategi Kepala Sekolah - Nur Hakim, Muhammad; Fitrayansyah, Rama (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to find out how the principal’s strategy, strategy planning in improving students' academic achievement at SMA Antarctica Sidoarjo. This study used a qualitative approach with descriptive analysis with the subject of principals, waka, curriculum, and teachers. The data collection techniques used are interviews, observations, and documentation studies. The validity of the data is tested by triangulation of sources and techniques. The data obtained is analyzed through data reduction, presentation, and verification. The results of this study show that 1) the principal's strategy in improving student academic achievement is carried out by developing resources, and creating academic achievement improvement programs, providing scholarships to students who have achievements, giving rewards to students and teachers who take part in competitions, and developing teacher competencies under their abilities in their fields. 2) Strategic planning is carried out by preparing a strategic plan, preparing a school budget work plan and conducting school self-evaluation and compiling programs within a period of 10 years and conducting madrasah self-evaluation every month.